Understanding transition from MDD to MDR - Chatwin, Linda (Henry Stewart Talks, 2017)
Overview of MDR, Transitioning from the MDD to the MDR, Notified Body Requirements, Interactions with Notified Bodies, UDI, Impact on EC Certifications